Responsabilidade social corporativa: o que há de filantrópico no trabalho voluntário? - Pithon, Conrado Farah Montenegro Caulliraux (2012)
The increasing business investment in the area of Corporate Social Responsibility (CSR) has provoked many questions, both in the academy and in the business field, on the need and the real reasons that lead organizations to encourage and disseminate social actions promoted in the community where are inserted. The objective of this study is to confront the discourse adopted on the practice of CSR in a multinational consulting company specializing in business management, with a business office in the city of Rio de Janeiro, Brazil, with the different perspectives of their employees about the reasons that they undertake such activities, as well as why its workforce decides to join them. In the construction of the theoretical basis, were used the existing streams of different visions on the topic of CSR. To investigate the possible inconsistencies between discourse and practice, was conducted a field research based on official documents and interviews with employees of both sexes and different positions in that company. The results suggest differences between the discourses within the employees, showing that they question the purpose of the company, as well as the philanthropic intentions of other coworkers.